ДО ПРОБЛЕМИ ІНСТИТУЦІОНАЛІЗАЦІЇ ДЕРЖАВНОЇ РЕГІОНАЛЬНОЇ ПОЛІТИКИ - Luchyk, V.E. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2011)
The paper deals with main problems of institutionalization of the state regional policy in Ukraine. The issues of development and functioning of the state institutions in the context of centre — regions relations are examined. Basic difficulties in implementation of the efficient state regional policy are described in connection with the absence of a unique central body to implement it.